Trends in major bleeding events in patients with acute coronary syndrome. (26th April 2021) - Cordero, A; Escribano, D; Bertomeu-Gonzalez, V; Quintanilla, MA; Moreno-Arribas, J; Perez-Berbel, P; Zuazola, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: bleeding events incidence has gained a crucial role in acute coronary patients (ACS) due to its independent effect prognostic value. Methods: we assessed trends of in-hospital and first-year-after-discharge major bleeding (MB) events in all ACS admitted in a single center between January 2009 and June 2019. MB was defined as those fitting definitions 3 or 5 of the BARC consortium. Patients were categorized as high-bleeding risk (HBR) according to the 2019 Academic Research Consortium HBR consensus if they met at least one major or two minor criteria. Inclusion period was divided in 3 groups: 2009-2012 (n = 884;29.5%), 2013-2015 (n = 1, 046; 34.9%); 2016-2019 (n= 1, 065; 35.6%). In-hospital MB was assessed by logistic binary regression and results are presented as odds ratio (OR); post-discharge MB were assessed by competing events regression models, taking all-cause mortality as a competing event, and results are presented as sub-hazard ratio (sHR). Results: we included 2995 patients, mean age was 68.5 (13.0), 26.2% females, 32.9% had diabetes and 42.4% STEMI. A total of 1, 163 (38.8%) were categorized as HBR patients. A non-significant trend to higher incidence of in-hospital MB was noted through the 3 time periods: 1.36%; 1.43%; 2.63 (p = 0.056) and it was mainly driven by the significant increase only in HBR patients: 2.54%; 4.60%; 7.67% (p = 0.002). Multivariate analysis identified age (OR: 1.06 95% CI 1.03-1.08, p < 0.001) and the time period 2016-2019 (OR: 1.93 95% CI 1.13-3.31; p = 0.017) as main variables associated to higher in-hospital MB. In contrast, postdischarge MB decreased over time periods: 6.0%; 4.59%; 2.07% (p < 0.01). The decreasing trend was mainly driven by the reduction of MB in HBR patients (figure). The competing risk regression analysis, adjusted by age, gender, previous cardiovascular disease, revascularization and medical treatments, identified an independent association between lower post-discharge MB risk and the time period 2016-2019 (sHR: 0.56 95% CI 0.35-0.90; p = 0.017). Conversely, diabetes (sHR: 1.52 95% CI 1.01-2.28) and previous heart failure (sHR: 2.42 95% CI 1.14-5.14) were associated to higher risk of MB. Conclusions: This continuous 10-year registry highlights the opposite trend of in-hospital vs. postdischarge MB that was mainly driven by reductions in HBR patients with ACS. The advances in post-discharge MB reductions should be take under consideration to prevent and avoid in-hospital MB.